PERHITUNGAN ONGKOS PRODUKSI MESIN PENCACAH RUMPUT PAKAN TERNAK TIPE AMP 1000 - Arthur G. D. Letelay; Rudy Poeng; Tertius V. Y. Ulaan (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2012)
In a machinery industry, to know the exact production cost of machine or machine component is essential. Using the data of production cost, the selling price of the product or the value of product making project can be calculated, then the profit can be determined. This research aim to calculate the total production cost of grass chopper machine, then using the result to determine the selling price and the profit. From the performed calculation we obtain that the selling price of the machine is Rp 9.234.016 per unit. This price is cheaper dan market price which has the value of Rp 13.300.000 per unit. Therefore, the net profit of this product is Rp. 1.995.000.